From Smart Grids to Microgrids: Advancements in Energy Infrastructure. - Ernest Hemingway, F. Scott Fitzgerald, Sherwood Anderson (International Journal of Innovative and Applied Finance, 2015)
login and register and pay the fees to get an open access to content